Guidelines for sustainable urban zero pollution community (S.U.Z.C) - Khattab, Mianda Khaled (AUC Knowledge Fountain, 2015)
The concept of sustainability has been introduced in the 1980s with the focus of environmental protection, where many developed and developing countries were and still are aiming to reach sustainability. Yet, with the increase of urbanization level, the tendency to meet the needs of the rising population is increasing without the focus of the environmental resources that are being abused in return. This leads to increasing the gap and the greed within the community between the rich people who can afford to abuse resources and the poor who can barely access their daily needs. This gap is concluded in an ignorant, negatively diversified and laid back community; in addition to threatening the upcoming generations about finding their needs in terms of natural resources being available for them. Solving this over looked problem is defined under applying sustainability concept for communities. Not only that but also presenting the full image of environmental and occupant’s impacts to prevent the greed behind the need of having a secured, resourceful living. The primary focus in this thesis was first to study novel approaches of zero pollution to implement within the application of sustainability concepts within the community. Starting with the tourism communities which are counted to be the primary income source to Egypt and some countries. The integration of sustainability concept with ecotourism communities via applying a zero waste concept is essential. Moving a step further, studying the effect of zero waste concept on the sustainable urban communities was another focus. This emphasis was considered after the realization of urbanization increase, which means more natural resources being abused. One further step is studying the environmental effect from urban communities was the next and main objective of this thesis topic. Urban communities affected the environment not only by solid wastes but also by water, energy and land usage; by this it is also affecting the sustainability of an urban community. Thus proposing several solutions to conserve water, utilize solid wastes, save energy and optimize land usage was the main focus. These proposed solutions are considered as novel approaches known as Zero Pollution, designed as guidelines to serve the urban community aiming at saving the environment. The proposed Sustainable Urban Zero Pollution Community (S.U.Z.C.) guidelines consists of 100 credits, that are hypothetically identified as a measuring tool, and focuses on three major segments for community guidance and evaluation. These segments are known as sustainable site management (36 credits), environmental management (44 credits) and a new integration of green team/ sustainability champions (20 credits). In addition to proposing guidelines for owners either residential or commercial buildings within the community, so as to ensure that everyone within the community is aware about the main objective and abiding to the sustainable community needs. These guidelines should serve and encourage the investing owners to act sustainably as the proposed community aims at. Two rating systems were also developed in this thesis, one for the community rating and the other is for the buildings’ owners’ evaluation and reward. The reward is reduction in operational cost for encouraged and participated owners towards sustainability as mentioned in Chapter 3 in this thesis. The proposed guidelines were compared with the widely used community rating system, LEED- ND which is more applicable for the developed countries. The comparative analysis was done and discussed in Chapter 4 in this thesis, and it is concluded that there are several advantages of the proposed guidelines for the S.U.Z.C over LEED-ND starting with being simple, focused, understandable and inexpensive to follow with easiness and efficiency points of focus being the main drivers for it. While also being purposeful about energy, water, air, materials and habitat as mentioned in chapter 3 in this thesis under several novel approaches. And this shall serve any developed and developing country, any new or existing community. Last but not least, Madinaty- New Cairo, a promising sustainable future urban community, was considered as the case study in this thesis. It is an application to the proposed guidelines to know how easy, understandable and applicable the guidelines are to users. The case study was evaluated based on the proposed guidelines points and rating system, and the evaluation is presented in Chapter 5 in this thesis. The conclusion of this section shows that Madinaty-New Cairo is in-line with the guidelines pre-requisites in terms of designing for green buildings, weighing the available landscape in rational proportions for infrastructure vs green areas vs corresponding parking spaces. In addition to meeting 54 credits out of the proposed 100 credits which qualifies Madinaty to a Bronze certification as per the proposed S.U.Z.C. rating system.